2012
DOI: 10.1159/000327144
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Visual Impairment in Older Adults in Mainland China: A Systematic Review and Meta-Analysis

Abstract: Purpose: This paper presents estimates of the prevalence of blindness and low vision among older adults over 50 years of age in mainland China. Methods: All primary reports of population-based studies that reported the prevalence or incidence of visual impairment among older populations in mainland China were identified. Twenty-four population-based studies were included in this systematic review. Blindness is defined as visual acuity of less than 3/60, or a corresponding visual-field loss to less than 10 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
1
14
2
Order By: Relevance
“…A meta-analysis including 24 population-based studies by Chen et al reported that the prevalence rates of blindness and low vision were 1.7% and 4.1%, respectively, among the older adults over 50 years of age in mainland China till 2010. [8] The studies estimating the prevalence of blindness and low vision in China published from January 2010 to April 2016 were searched and presented in Table 6. [4,920] Although the estimating criteria for blindness and low vision differed among studies, Table 6 shows that according to the BCVA in better eye, previous studies reported that the prevalence rates of blindness and low vision were 0.2% to 2.88% and 1.4% to 10.41% in China, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including 24 population-based studies by Chen et al reported that the prevalence rates of blindness and low vision were 1.7% and 4.1%, respectively, among the older adults over 50 years of age in mainland China till 2010. [8] The studies estimating the prevalence of blindness and low vision in China published from January 2010 to April 2016 were searched and presented in Table 6. [4,920] Although the estimating criteria for blindness and low vision differed among studies, Table 6 shows that according to the BCVA in better eye, previous studies reported that the prevalence rates of blindness and low vision were 0.2% to 2.88% and 1.4% to 10.41% in China, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of VI in China is 0.94%, yet, for the people older than 50, this figure rises to 5.8%. In Tibet, one of the highest and harshest human habitations on earth, the prevalence is 13.2% 6–8…”
Section: Introductionmentioning
confidence: 99%
“…Data from the World Health Organization (WHO) showed that cataract accounted for approximately 50% of blindness worldwide [1]. In China, blindness and low vision affects about 5.8% of Chinese aged 50 and above [2]. Given the rapid population aging and high prevalence of age-related cataract (ARC) in China, especially in rural areas [3,4], it is expected that an increasing number of population will suffer from cataract.…”
Section: Introductionmentioning
confidence: 99%